Transformational leadership and work outcomes: organizational justice as mediator - Rokhman, Wahibur; Hassan, Arif (World Business Institute, 2012)
The study explored the relationship of transformational leadership with organizational justice and work outcomes. Specifically the study examined the potential role of procedural justice as mediator of transformational leadership and work outcomes, namely, job satisfaction, organizational commitment, and turnover intention. Sample consisted of 370 employees from 60 institutions of Islamic microfinance in Indonesia. The empirical tests indicated that transformational leadership contributed significantly to procedural justice perceptions as well as to the three work outcomes. Also, procedural justice had significant effect on all the three work outcomes. The test of mediation effect of procedural justice on transformational leadership and work outcome relationship indicated no significant mediating effect on job satisfaction and turnover intention, though it was partially significant with organizational commitment